The prevalence of antibiotic resistance in aerobic and anaerobic bacteria isolated from patients with diabetic foot ulcers - Khalida Jhalil Ibraheem (College of Pharmacy / Mustansiriyah University, 2012)
The aim of the present study was to determine the microbiological profile and antibiotic susceptibility patterns of organisms isolated from diabetic foot ulcers. Pus and debrided tissue samples from 46 patients with diabetic foot ulcers collected and processed. Bacterial isolates were identified by using different microscopical examination, cultural characteristics and biochemical tests. Sensitivity tests were performed by Kirby-Bauer disk diffusion method. Out of 46 patients , male (73.9%) were found to be affected and develop foot infection more than female (26.1%) while type two diabetes mellitus (65.2%) more susceptibility for infection than type one (34.8%). Gram- negative bacteria were most frequently isolated (42%), followed by gram-positive aerobes and anaerobes (30.4% and 27.6% respectively). Predominant aerobic and anaerobic bacteria were Staphylococcus aureus (17.1%) and Peptostreptococcus spp (8.6%), respectively. All the microorganisms isolated showed high resistance to used antibiotics; susceptibility of both aerobic and anaerobic bacteria to ceftizoxime was (100%), so we suggest this drug for treatment of diabetic foot ulcers